TbMP42 is a structure-sensitive ribonuclease that likely follows a metal ion catalysis mechanism - Niemann, Moritz (Oxford University Press, 2008)
RNA editing in African trypanosomes is characterized by a uridylate-specific insertion and/or deletion reaction that generates functional mitochondrial transcripts. The process is catalyzed by a multi-enzyme complex, the editosome, which consists of approximately 20 proteins. While for some of the polypeptides a contribution to the editing reaction can be deduced from their domain structure, the involvement of other proteins remains elusive. TbMP42, is a component of the editosome that is characterized by two C(2)H(2)-type zinc-finger domains and a putative oligosaccharide/oligonucleotide-binding fold. Recombinant TbMP42 has been shown to possess endo/exoribonuclease activity in vitro; however, the protein lacks canonical nuclease motifs. Using a set of synthetic gRNA/pre-mRNA substrate RNAs, we demonstrate that TbMP42 acts as a topology-dependent ribonuclease that is sensitive to base stacking. We further show that the chelation of Zn(2+) cations is inhibitory to the enzyme activity and that the chemical modification of amino acids known to coordinate Zn(2+) inactivates rTbMP42. Together, the data are suggestive of a Zn(2+)-dependent metal ion catalysis mechanism for the ribonucleolytic activity of rTbMP42.